The New international commentary on the New Testament : The Epistles of John - Marshall, I. Howard (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 1978)
The three Epistles of John, according to the author, are concerned with the fundamentals of Christian belief and life -- faith and love. The reader who grasps the message of these short but essential letters will have a sound basis in Christian doctrine. This group of Epistles is also a good starting point for the study of the Gospel of John. This important commentary was written not only so that students of the Bible might master the content of John's Epistles, but that they might come to a proper understanding of Johannine theology as a whole.
The situation and character of 2 and 3 John -- The situation of 1 John -- The structure of 1 John -- Theories of rearrangement and redaction -- Relationships between the Johannine writings -- The authorship of the epistles -- The early history of the epistles in the church -- The thought of the epistles -- Address and greeting -- Living in truth and love -- Beware of false teaching -- Final words and greetings -- Address and greeting -- The writer praises Gaius -- The writer denounces Diotrephes -- The writer praises Demetrius --
Includes bibliographical references (pages xv-xvii) and indexes.
Keywords: Bible. -- Commentaries; Bible. Epistles of John - Commentaries; Bible -- N.T -- Epistles of John -- Commentaries